The Novel as Art: Perspectives From Bakhtin and Lawrence - Kafle, Chiranjibi (Tribhuvan University Journal, 2010)
Literary world continued to face a clash of opinion for long as to whether the popular genre, the novel, should be regarded as representing artistic literary heritage. As literary scholarship often traced a line separating poetic discourse from the novelistic discourse, readers as well as scholars were in a state of dilemma whether to recognize the novel as artistic genre. However, with authors like DH Lawrence and critics like Mikhail Bakhtin, the confusion no longer needs to hound us. This article is an attempt to see why and how the novelistic discourse is fit enough tobe considered artistic discourse and the novel an artistic genre of literature. As a methodology to look into the issue, scholarly perspectives forwarded by Mikhail Bakhtin and DH Lawrence have been taken into consideration. Bakhtin’s concept of ‘heteroglossia’ and Lawrence’s ‘wholeness of life’ have been adopted as the basic theoretical tool while the textual references are mainly based on their essays entitled “Discourse in the Novel” and “Why the Novel Matters,” respectively. The article concludes that Bakhtin's appreciation of novelistic discourse as something that enabled the "representation of heteroglossia…," and Lawrence's description of the novel as the “book of life” are both equally potent scholarly defenses establishing the novel as artistic genre.